PENGARUH STRATEGI PDR TERHADAP ACTIVE LEARNING DAN KEMAMPUAN BEKERJASAMA ANAK USIA DINI - ayu asmah; yulianti yulianti (Universitas Muhammadiyah Surabaya, 2016)
ABSTRACT The aim of this paper is to know the effect of Plan Do Review (PDR)on early childhood students’ active learning and ability to cooperate. Quantitative design used in this research with nonequivalent control group design. The data were gathered through observation and documentation. The gathered data were analyzed using ANOVA and MANOVA. The findings showed that (1) test result of PDR strategy (variable X) on active learning (variable Y1) has significant effect at level 0.04 < 0.05 ; (2) the test result of PDR strategy on ability to cooperate variable (Y2) has significant effect at level 0.06 < 0.05; (3) test result using Hottelling’s trace of PDR strategy on active learning and ability to cooperate showed significant at level 0.001 < 0.05. It is suggested for the early childhood institution to promote learning through student centered approach, teacher should more creative and innovative in developing learning that suitable with the students needs and interests. Keywords: PDR strategy; active learning; cooperate ability